1984
DOI: 10.1107/s0108270184010507
|View full text |Cite
|
Sign up to set email alerts
|

catena-Poly{μ-(2,2'-bipyrimidine-N,N':N'',N''')-[(nitrato-O,O')copper(II)]-di-(μ-nitrato-μ-O)-[(nitrato-O,O')copper(II)]}, [Cu2(NO3)4(C8H6N4)]

Abstract: 2030[NH2(CH3)214 [MosO26].2CaHTNO octamolybdate structures it is evident that the bonding within a cluster is controlled in the first place by the dominant influence of the strong bonds in the cis Mo(Ot) 2 groups. The weak internal bonds through oxygen bridges are complementary and can vary in length and direction to meet the needs of a particular structure. 14, 584-604.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…The average C−C and C−N bond distances in the rings of this ligand are 1.42(1) and 1.35(1) Å for compounds 1 − 3 . These values are in good agreement with those currently given in the literature for this ligand. …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The average C−C and C−N bond distances in the rings of this ligand are 1.42(1) and 1.35(1) Å for compounds 1 − 3 . These values are in good agreement with those currently given in the literature for this ligand. …”
Section: Resultssupporting
confidence: 91%
“…These values are in good agreement with those currently given in the literature for this ligand. [19][20][21] Infrared Spectroscopy. The most important aspects containing the infrared spectra of 1-3 deal with the possibility to distinguish between the chelating and bis-chelating coordination modes of bpm and to characterize the presence of the different coordination modes of the pseudohalide ligands.…”
Section: Description Of the Structure Of [Mn 2 (Bpm) 3 (Ncs) 4 ] (1)mentioning
confidence: 99%
“…In recent years, particular attention has been devoted to the synthesis and crystal structure determination of bpm-containing copper(II) complexes. In these compounds, both bidentate (Morgan, Pennington, Petersen, Ruminski, Bennett & Rommel, 1992;De Munno et al, 1990; and the bis-bidentate (De Munno & Bruno, 1984;Julve et al, 1988; 1993) coordination modes were found. Recently, our attention has focused on dinuclear compounds of bpm with other first-row transition-metal ions to discuss and compare the magnitude of the exchange coupling through the bridging bpm ligand.…”
mentioning
confidence: 95%
“…It can coordinate to metal centres either as a bis-chelate (De Munno & Bruno, 1984;De Munno, Julve, Nicol6, Lloret, Faus, Ruiz & Sinn, 1993;Brewer & Sinn, 1985;Kaim & Kholmann, 1987;Brewer, Murphy & Petersen, 1987;Julve, De Munno, Bruno & Verdaguer, 1988;Julve, Verdaguer, De Munno, Real & Bruno, 1993) or a chelate (Castro, Julve, De Munno, Bruno, Real, Lloret & Faus, 1992;De Munno, Bruno, Julve & Romeo 1990;De Munno, Julve, Lloret, Faus, Verdaguer & Caneschi, 1993;Hiskey & Ruminski, 1986;Ruminski & Petersen, 1985;Matsubayashi, Yamaguchi & Tanaka, 1988). In recent years, particular attention has been devoted to the synthesis and crystal structure determination of bpm-containing copper(II) complexes.…”
mentioning
confidence: 99%